UTILIZATION POSSIBILITIES OF THE HYBRID DRIVE IN LAND TRANSPORT (Perner's Contacts, 2010)
Utilization possibilities of hybrid drive in land transport in this paper will be described
Keywords: hybrid drive; hybrid vehicle; rail transport; road transport; power transmission